The Perpignan-Figueras high-speed line. A great European project that arrived in the middle of a crisis and in an immature environment. - Papaghiannakis, Petros (Trialog Publishers, 2020)
The Perpignan-Figueras high-speed line is one of the major European projects aimed at solving technical barriers and bottlenecks between rail networks. It is an interoperable line designed for mixed passenger and freight traffic, built perfectly on time. Delivered into commercial service in December 2010, it arrived in the middle of a global financial crisis and in an immature and incomplete railway environment. The situation is improving, but the line is still underutilized. Perspectives are good, but efforts are necessary, both on the infrastructure side, operators' and on the authorities' side, to set up regional trains.
Keywords: Hochgeschwindigkeitsverkehr; Hochgeschwindigkeitsstrecke; Eisenbahnverkehr; Transeuropäisches Netz; Güterfernverkehr; Personenfernverkehr; Verkehrsinfrastruktur; Großprojekt; Baufertigstellung